Micropropagation of Alibertia edulis Rich - Silva, Fernanda Augusta Boato da (2008)
The aim of this work was to develop a micropropagation protocol for Alibertia edulis, a medicinal Brazilian Cerrado plant. A. edulis seeds were sterilized and germinated in water-agar. Fifteen millimeter long explants from the seedlings cultivated for 50 days were used for the multiplication in three consecutive subcultures. The cytokinin benzyladenine (BA) alone or combined with indole-3-butyric acid (IBA) was added to ¼ MS medium. The treatments containing combinations of the BA + IBA induced more shoot proliferation than the BA alone, with the optimum concentration of 0.5 mg.L-1 for both growth regulators. A. edulis shoots elongated easily and the presence of growth regulators did have a positive effect on the shoot elongation. Consecutive subcultures also had a positive effect on both sprouting and shoot elongation. Activated charcoal was essential for rooting, and all rooted plants were able to acclimatize.